Can financial inclusion improve children's learning outcomes and late school enrolment in a developing country?. Issue 3 (14th January 2023) - Koomson, Isaac; Afoakwah, Clifford
ABSTRACT: This study uses comprehensive household data from Ghana to examine the link between financial inclusion and children's learning outcomes and late school enrolment. After resolving endogeneity, we find that a standard deviation increase in financial inclusion is associated with 0.7882 to 0.9504 standard deviations increase in children's learning outcomes. It also reduces late school enrolment by 0.9493 standard deviation. Financial inclusion enhances learning and schooling outcomes more for girls and urban children. These findings are robust to different indicators of learning outcomes and alternative approaches to addressing endogeneity. Parents' ability to spend on extra classes and on books and other school-related supplies serve as possible channels through which financial inclusion affects children's educational outcomes.